Aircraft propulsion - Farokhi, Saeed (Wiley, 2014)
"Aircraft Propulsion, Second Edition is a comprehensive textbook covering aircraft gas turbine engine and rocket propulsion from the basic principles to more advanced treatments in engine components"--